2008
DOI: 10.1111/j.1742-1241.2008.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel programme to evaluate and communicate 10-year risk of CHD reduces predicted risk and improves patients’ modifiable risk factor profile

Abstract: Aims We assessed whether a novel programme to evaluate/communicate predicted coronary heart disease (CHD) risk could lower patients' predicted Framingham CHD risk vs. usual care. Methods The Risk Evaluation and Communication Health Outcomes and Utilization Trial was a prospective, controlled, cluster-randomised trial in nine European countries, among patients at moderate cardiovascular risk. Following baseline assessments, physicians in the intervention group calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 72 publications
(117 reference statements)
2
55
0
1
Order By: Relevance
“…Few studies have evaluated the impact of using global cardiovascular risk assessment in clinical practice. These studies reported either moderate effects (a modest increase in drug prescription or reduction in risk factors), or a lack of effect (Benner et al, 2008;Brindle et al, 2006;Sheridan and Crespo, 2008;van Steenkiste et al, 2008). Our results showed that if cardiovascular clinical decision rules relying on global cardiovascular risk assessment could improve health outcome, the use of biomedical risk functions without consideration of psychosocial status could increase health inequalities in depressive subjects.…”
Section: Discussionmentioning
confidence: 83%
“…Few studies have evaluated the impact of using global cardiovascular risk assessment in clinical practice. These studies reported either moderate effects (a modest increase in drug prescription or reduction in risk factors), or a lack of effect (Benner et al, 2008;Brindle et al, 2006;Sheridan and Crespo, 2008;van Steenkiste et al, 2008). Our results showed that if cardiovascular clinical decision rules relying on global cardiovascular risk assessment could improve health outcome, the use of biomedical risk functions without consideration of psychosocial status could increase health inequalities in depressive subjects.…”
Section: Discussionmentioning
confidence: 83%
“…Other CVD primary prevention studies achieved larger effects but required greater resources, and many included multiple contacts with clinicians. 8,10,11,[21][22][23][24] If a measurable positive effect of a more limited intervention like ours can be accomplished at a sufficiently low cost, it may be a worthwhile approach to adopt. If the process of delivering these messages can be fully automated (such as using a patient portal connected to the electronic health record), this may reduce the cost of providing this service further.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that physicians need to reinforce messages in order achieve a significant reduction in CHD risk as reported in other studies. 16 For this study, we used the 4-year CHD risk model developed by D'Agostino and colleagues from Framingham data. 15 It has the advantage of being applicable to all patients because it calculates risk of either a primary or a secondary CHD event.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline 10-year risk was 17 % with a calculated standard deviation of 0.07 % for the intervention group (n=524). 16 For our 4-year risk outcome, we assumed a 7 % baseline risk with standard deviation of 0.035 %. To be able to detect a 20 % relative risk reduction, a sample size of 105 subjects per group achieves 80 % power (two-sided Mann-Whitney test) with α=0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation